2008
DOI: 10.2337/db07-1541
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Stimulation of Cyclin A2 in β-Cell Proliferation

Abstract: OBJECTIVE-␤-Cell proliferation is an important mechanism underlying ␤-cell mass adaptation to metabolic demands. We have examined effects, in particular those mediated through intracellular cAMP signaling, of the incretin hormone analog exendin-4 on cell cycle regulation in ␤-cells.RESEARCH DESIGN AND METHODS-Changes in islet protein levels of cyclins and of two critical cell cycle regulators cyclin kinase inhibitor p27 and S-phase kinase-associated protein 2 (Skp2) were assessed in mice treated with exendin-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 42 publications
11
53
0
Order By: Relevance
“…To further improve differentiation conditions from pancreatic progenitor to β cells, exendin-4, a glucagon-like peptide-1 agonist, and SB431542, a TGF-β signaling inhibitor, were added to stage 3 progenitor cells. Both of these additions enhanced the differentiation efficiency of β cells to 4.6% and 8.2% (C-peptide + ), respectively, consistent with previous observations (21)(22)(23). A combination of exendin-4 and SB431542 treatment from day 9 to day 12 produced the highest percentage of β cells (15%) ( Figure 2D).…”
Section: Gck Mutations Specifically Affect Glucose-mediated Insulin Ssupporting
confidence: 90%
“…To further improve differentiation conditions from pancreatic progenitor to β cells, exendin-4, a glucagon-like peptide-1 agonist, and SB431542, a TGF-β signaling inhibitor, were added to stage 3 progenitor cells. Both of these additions enhanced the differentiation efficiency of β cells to 4.6% and 8.2% (C-peptide + ), respectively, consistent with previous observations (21)(22)(23). A combination of exendin-4 and SB431542 treatment from day 9 to day 12 produced the highest percentage of β cells (15%) ( Figure 2D).…”
Section: Gck Mutations Specifically Affect Glucose-mediated Insulin Ssupporting
confidence: 90%
“…This conclusion is further supported by our demonstration that transient overexpression of NUPR1 reduced the rate of MIN6 beta cell proliferation in parallel with inhibiting expression of the cell cycle regulators Ccna2 and Tcf19 through effects to suppress their promoter activities in beta cells. The Ccna2 gene regulates progression at both the G1/S and G2/M checkpoints of the cell cycle [27,28] and lentiviral-mediated infection of islets to overexpress Ccna2 stimulates beta cell self-replication [20]. The TCF19 protein contains a sequence exhibiting characteristics of transcription factors and its expression is regulated in the late stages of the cell cycle [21], consistent with it playing a regulatory role in the expression of genes necessary for cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased islet mass with Nupr1 deletion, attention was focused on genes known to regulate the cell cycle. Messenger RNAs for cyclin A2, which has been identified as a target in the regulation of beta cell mass [20], and TCF19, which has been implicated in regulating genes involved in the later stages of cell cycle progression [21], emerged as possible candidates. Our array analysis indicated that Ccna2 and Tcf19 mRNAs were increased by 1.6-fold (p <0.0004) and 1.9-fold (p =0.00002), respectively, in Nupr1 −/− islets.…”
Section: Metabolic Characterisation Of Nupr1mentioning
confidence: 99%
“…Previous studies have implicated both cAMP- (Buteau et al 2003, Song et al 2008) and b-arrestin (Talbot et al 2012)-dependent mechanisms in the proliferative effects of GLP1 on pancreatic b-cells. In addition, it has been reported that the proliferative action of GLP1 is mediated by the transactivation of epidermal growth factor receptor (EGFR; Buteau et al 2003) or the increased expression and activation of the insulin-like growth factor 1 receptor (IGF1R) (Cornu et al 2010) both of which result in the activation of the PI3K/protein kinase B (PKB) pathway.…”
Section: Introductionmentioning
confidence: 99%